The PrEP recommendation: the inscribed disease in a healthy body - Simone Wolfgang; Denise Portinari (Social Medicine Publication Group, 2020)
In July 2014, the World Health Organization (WHO) recommended that all gay men join the "pre exposal medication Truvada" as a valid resource to prevent HIV. The PrEP, prophylaxis consists in taking a combination of antiretroviral medication once a day, in order to prevent HIV infection. The WHO promotion of a policy that recommends all HIV negative gay men to join the PrEP, may be seen, in the context of contemporary biopolitical techniques and strategies, as a form of control and medicalization of homosexual bodies and practices. It´s important to explicit the life-related effects linked to a measure like the PrEP program, considering this as a paradigm shift in HIV/Aids strategies. The shift involves the gradual substitution of the "condom use" recommendations for the use of permanent prophylactic medications, and may be understood as a move away from the abstinence paradigm - sexual behavior control - to a more contemporary form of individual medicalized body biocontrol, as outlined by Foucault in his later texts. This measure also exposes a delicate aspect of the social conduction of the HIV/Aids epidemics: the stigmatization related to the gay community as the ultimate risk group. Affirming that every homosexual should take the PrEP pill, may have the effect of perpetuating the idea that gay men are the main vector of this disease. Among the misconceptions that this may involve are the perpetuation of prejudice related to Aids and gay men, leading heterosexual populations to believe that they are not connected in the epidemic chain.